Susceptibilidade de Digitonthophagus gazella (Fabricius : 1787) (Coleoptera: Scarabaeidae) aos reguladores de crescimento de insetos (IGRs) Diflubenzuron e Methoprene em Uberlândia, MG - Domingues, Luísa Nogueira (2007)
The Insect Growth Regulators are considered more selective than the conventional insecticides, are not toxic to mammals if used in the recomended dose and are easily degradable in environment. Diflubenzuron and Methoprene are IGRs from the chitin sinthesis inibithors and juvenile hormones analogs classes, respectively. These IGRs show comprovated eficience against Haematobia irritans, one of the most important bovine ectoparasite. Digitonthophagus gazella is a natural enemy of H. irritans because it changes the structure and bury the bovine feces, habitat of the imatures stages from this parasite. The purposes of this work were to measure the suceptibility of adults and imatures of D. gazella to the IGRs Diflubenzuron e Methoprene, analyse the interference of this insecticides in the progeny production, verify the action of the insecticides in the duration of the life cicle and in the sex ratio of beetles that have been exposed along all their development cicle and analyse, according the IOBC (International Oranization for Biological Control), the toxicity of the IGRs to the beetle D. gazella. Pairs of beetles were placed in buckets partially filled with humid soil and were fed with bovine feces containing 1, 0,5 and 0,2 ppm of Diflubenzuron and 0,2 ppm of Methoprene, during the time necessary to oviposition and development of the progeny. Thereafter, they were recovered by pitfall traps, as well as their respective progenies. The IGRs not affected the survival of the adults inicially exposed, but interfered on the production of their progenies according to the methodology used. Diflubenzuron 1 and 0,5 ppm also interfered in the duration of the life cicle of the beetles. None of the tested concentrations of the IGRs modified the sex ratio of the beetles progenies. Diflubenzuron tested concentrations showed to be moderately harmful to the beetles whereas Methoprene 0,2 ppm was only slightly harmful, according to the IOBC.